The Effect of Income Inequality, Women's Empowerment, Unemployment and Population Density on Poverty in Aceh Province - Mahendra, Weri; Wibowo, Muhammad Ghafur (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2023)
This study aims to analyze the effect of income inequality, women's empowerment, unemployment, and population density on poverty levels in Aceh Province during 2017-2020. This study uses secondary data from 2017-2020 from the Central Statistics Agency (BPS) of Aceh Province. The research method uses panel data regression analysis techniques, with the best model selection test obtained being the fixed effect model (FEM). The results showed that the variables of women's empowerment and population density significantly negatively affected the level of poverty. Meanwhile, income inequality and unemployment variables had no effect on the poverty level in Aceh Province in 2017-2020.